The impact of manipulation phase feeding system on the broiler performance and carcass lipid profile: A review - Hamdeen Yahia Dawood Rahoma (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
This article intended to include the effect of manipulation phase feeding systems on broiler performance and carcass-serum lipids. The results of many different research studies were conducted to evaluate the effect of different phase feeding. The result showed that broiler performance was not affected but fat deposition and cholesterol, total feed intake was significantly reduced by the different phase feeding programs. So, we can conclude that phase feeding is one of the methods to reduce fat deposition and cost by controlling the amount of feed intake.